CASE REPORT: MANDIBULAR CANINE WITH 2-1 CONFIGURATION (International Journal of Food and Nutritional Sciences, 2022)
Endodontic treatment success is largely dependent on the clinician's understanding of and aptitude for dealing with atypical anatomy. The mandibular canine typically has one root and one canal, however, 15% of individuals may have two canals and one or more foramina, and even fewer individuals may have two roots. In this paper, a clinical case is reported of a mandibular canine with two root canals that converge into a single canal and one foramen.